The Multifaceted Roles of CHROMR in Innate Immunity, Cancer, and Cholesterol Homeostasis - Emma R. Blaustein; Coen van Solingen (Non-Coding RNA)
CHROMR is a primate-specific long noncoding RNA with emerging roles in homeostasis and pathophysiology. Elevated blood levels of CHROMR have been observed in patients with cardiovascular disease and several cancers, where it is correlated with poor clinical outcomes. Like many lncRNAs, CHROMR accumulates in both the nucleus and the cytoplasm, and it assumes distinct functions in each of these cellular compartments. In the nucleus, CHROMR sequesters a transcriptional repressor complex to activate interferon-stimulated gene expression and antiviral immunity. In the cytoplasm, CHROMR competitively inhibits microRNAs involved in cholesterol efflux and cell cycle regulation, thereby impacting gene pathways involved in reverse cholesterol transport, HDL biogenesis, and tumor growth. In this review, we detail the multifaceted functions of CHROMR in cholesterol metabolism, innate immunity, and cancer progression. We also explore the potential molecular mechanisms that govern its expression and dynamic subcellular localization, which may be key to its functional versatility. Advancing our understanding of the regulatory networks and cellular environments that shape CHROMR activity will be critical for assessing its promise as a therapeutic target and diagnostic biomarker.